1997
DOI: 10.1002/(sici)1098-1136(199709)21:1<124::aid-glia14>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The glial glutamate transporter in hyperammonemia and hepatic encephalopathy: Relation to energy metabolism and glutamatergic neurotransmission

Abstract: Abnormalities in glutamate metabolism and glutamatergic neurotransmission appear to play a major role in the pathogenesis of hyperammonemia and hepatic encephalopathy. Astrocytes may be involved in these derangements as ammonia has been shown to impair the ability of these cells to take up glutamate. This study presents a northern blot analysis of the GLT-1 glutamate transporter in hyperammonemic rats, and in rats with thioacetamide-induced acute liver failure. Our findings demonstrate a downregulation of GLT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This could be an alternative explanation for the observed correlation between GLT and APP expression (Li et al, 1997) and would be in agreement with the reports on reduced density of glutamate receptors in AD (e.g., Greenamyre et al, 1985;Chalmers et al, 1990;Dewar et al, 1991;Scheuer et al, 1996). In addition to amyotrophic lateral sclerosis Lin et al, 1998), low GLT levels have been found in liver coma (Knecht et al, 1997;Norenberg et al, 1997). The control sample in our material with the lowest GLT level (but the highest level of GLAST) is case #2 (Fig.…”
Section: Pathological Significance Of Reduction In Glutamate Uptakesupporting
confidence: 91%
“…This could be an alternative explanation for the observed correlation between GLT and APP expression (Li et al, 1997) and would be in agreement with the reports on reduced density of glutamate receptors in AD (e.g., Greenamyre et al, 1985;Chalmers et al, 1990;Dewar et al, 1991;Scheuer et al, 1996). In addition to amyotrophic lateral sclerosis Lin et al, 1998), low GLT levels have been found in liver coma (Knecht et al, 1997;Norenberg et al, 1997). The control sample in our material with the lowest GLT level (but the highest level of GLAST) is case #2 (Fig.…”
Section: Pathological Significance Of Reduction In Glutamate Uptakesupporting
confidence: 91%
“…Knecht and co-workers (1997) showed significant down-regulation of EAAT-2 protein and mRNA in frontal cortex of ALF comatose rats compared to sham operated controls (Knecht et al 1997). A significant decrease of EAAT-2 mRNA levels was demonstrated in brain tissues from rats with thioacetamide (TAA)-induced ALF and of hyperammonemic rats by northern blot analyses (Norenberg et al 1997). Prolonged treatment of cultured rat astrocytes with ammonia has been shown to induce an increase in extracellular glutamate (Ohara et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic encephalopathy (HE) is a complex neurological disorder associated with acute or chronic liver failure in which ammonia is a major neurotoxin (Norenberg, 1996;Butterworth, 1997;Albrecht, 1998). Repeated (2-3 times) administration to rats or mice of a hepatotoxin, thioacetamide (TAA), at 24-hr intervals is a routine procedure to induce neurophysiological symptoms and changes in blood and brain biochemistry and brain morphology characteristic of acute HE (Trennery and Waring, 1983;Albrecht and Hilgier, 1984;Albrecht et al, 1988;Zimmermann et al, 1989;Peeling et al, 1993, Hilgier andOlson, 1994;Norenberg et al, 1997). However, the course of HE after cessation of the treatment has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%